Marketing strategy of Camp Zagreb - Šimunić, Dora; Miškulin, Ana (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
The paper focuses on Camp Zagreb in Sveta Nedelja, thoroughly analyzing strategies for extending the tourist season and attracting guests outside the traditional seasons. The current state analysis reveals that the campsite has a favourable geographic location, making it easily accessible to guests, mainly due to its proximity to major roads and the airport. However, a lack of clear vision and weaknesses in the marketing strategy were also identified. The SWOT analysis highlights key strengths, such as a favourable location and affordable prices, and weaknesses, like the need for a clear vision and an adequate marketing strategy. Improvement suggestions focus on strengthening the marketing strategy by using social media as a critical tool for communication with potential guests. Additionally, interactive initiatives, such as an eco-market and the 'Leave Your Mark' initiative, need to be implemented, which would attract guests through educational and eco-conscious activities. This research paper can potentially contribute to sustainable tourism development and enhance the destination's competitiveness outside traditional seasons. By implementing the proposed strategies, Camp Zagreb can become a more appealing destination for a broader range of guests and contribute to the development of the local community.